2020
DOI: 10.1002/agj2.20287
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service delivery by cover crop mixtures and monocultures is context dependent

Abstract: While cover crops and mixtures are increasingly used to provide ecosystem services in agroecosystems, some fundamental questions remain about how cover crop performance and composition vary in different conditions, limiting optimal cover crop use. We conducted a field experiment at a research farm in New York, including a subset of treatments in three working farm fields. We selected two common cover crops, hairy vetch (Vicia villosa Roth), a legume, and common wheat (Triticum aestivum L.), a grass, with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Legume cover crops, on the other hand, can be more effective at providing additional N through biological N fixation, which will improve soil fertility and cash crop productivity. Therefore, to maximize the multiple benefits of cover crops use, mixtures of legume/grass species have also been recommended (Finney et al., 2017; Reiss & Drinkwater, 2020). Mixtures of legume and grass cover crop species can enhance biomass accumulation relative to monocultures, as legumes provide additional N needed by grasses (Blesh et al., 2019; Brennan & Smith, 2005; Jian et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Legume cover crops, on the other hand, can be more effective at providing additional N through biological N fixation, which will improve soil fertility and cash crop productivity. Therefore, to maximize the multiple benefits of cover crops use, mixtures of legume/grass species have also been recommended (Finney et al., 2017; Reiss & Drinkwater, 2020). Mixtures of legume and grass cover crop species can enhance biomass accumulation relative to monocultures, as legumes provide additional N needed by grasses (Blesh et al., 2019; Brennan & Smith, 2005; Jian et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides production of food, agroecosystems can supply ecosystem services such as nutrient cycling, carbon sequestration, pollination and biological control (Swinton et al 2007;Zhang et al 2007;Bommarco et al 2013). These services could help reduce the impact of agriculture on the environment and the climate, as well as sustaining agricultural production in the long-term (Bommarco et al 2013;Lal 2019;Reiss & Drinkwater 2020). Neglecting the importance of supporting and regulating functions in agroecosystems may lead to negative impacts on both the agroecosystem itself and surrounding ecosystems, e.g.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Perennial legumes may deposit N that can be recovered by grasses in cover crop mixtures (Schipanski and Drinkwater 2012). Reiss and Drinkwater (2020) reported no difference in the amount or the proportion of legume N derived from N 2 fixation in a cover crop mixture compared to the same legumes as sole cover crop. Frankow-Lindberg et al (2009) showed that mixtures of forage crops have a higher ability to suppress weeds but also pointed out red clover as a weaker competitor.…”
Section: Forage Crops-cash Crop Phasementioning
confidence: 99%